PHUBBING BEHAVIOR IN YOUNG GENERATION - Eny Ratnasari; Fikri Dwi Oktaviani (Metakom, 2020)
Phubbing is a phenomenon that occurs due to technological development. Unconsciously, this happens in human interactions in everyday life. This study wants to find out whether there is a relationship between cell phone addiction and social media addiction on phubbing behavior on young generation. The hypothesis proposed is the relationship between mobile addiction and social media with phubbing behavior. This research uses quantitative research methods with the type of correlational research. Research data collection is done by using the online survey method through Google forms. Respondents were selected by purposive sampling technique. The characteristics of the research subjects are the younger generation who live in Java Island, participating between 17-25 years, actively using mobile phones and social media for more than 8 hours a day. The number of samples used as research subjects were 177 participants. The results of data analysis showed the value of the conversion coefficient of (r) 0.680 with sig. 0,000 (p <0.01). The conclusion from this study is a positive relationship between mobile addiction and social media with a phubbing relationship. The higher the cell phone addiction and social media addiction, the higher the phubbing interaction. The contribution of mobile and social media addiction to phubbing behavior was 46.2%. While the remaining 53.8% is another factor not included in the study.